2022
DOI: 10.1021/acsami.2c00244
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Ion Mobility in Solid Polymer Electrolytes Using Hollow Polymer Nanospheres as an Additive

Abstract: Solid polymer electrolytes (SPEs) possess improved thermal and mechanical stability as safe energy storage devices. However, their low ion mobilities and poor electrochemical stabilities still hinder the wide industrial application of SPEs. Herein, we introduce an SPE design that provides an enormous number of electrochemically stable pathways and space for lithium-ion transport, blending polymer (polydopamine) hollow nanospheres with an inactive inorganic template into a poly­(ethylene oxide) (PEO) and lithiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Li et al [ 100 ] prepared HPDA fillers, as shown in Fig. 2 a, in which hollow silica was used as a template and covered with a layer of polydopamine.…”
Section: Overview Of Composite Polymer Electrolytesmentioning
confidence: 99%
See 3 more Smart Citations
“…Li et al [ 100 ] prepared HPDA fillers, as shown in Fig. 2 a, in which hollow silica was used as a template and covered with a layer of polydopamine.…”
Section: Overview Of Composite Polymer Electrolytesmentioning
confidence: 99%
“…Adapted with permission from Ref. [ 100 ]. c Schematic of dopamine on the surface of LLZTO particles; d Arrhenius log 1000/ T of LLZTO@PDA-PEO and LLZTO/PEO CPEs.…”
Section: Overview Of Composite Polymer Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the inorganic fillers can establish a rigid and interfacial cross-linked skeleton of PEO matrices, which is able to improve the mechanical and thermal stability of CPEs. Apart from the structural features (e.g., size and morphology), the surface characteristic of the fillers plays a crucial role in the homogeneous interface properties and kinetic transport behaviors of CPEs. , It is highly desirable to design and synthesize inorganic fillers that can afford rich types of Lewis acid–base interactions with either PEO chains or Li salt, including hydrogen-bond interaction, positive vacancy-salt interaction, and dipole–dipole interaction . For example, Wieczorek et al elucidated the Lewis acid–base theory that the acidic surface sites of the Al 2 O 3 filler have strong affinity with ClO 4 – and promote the dissociation of LiClO 4 to release Li + .…”
Section: Introductionmentioning
confidence: 99%